ELECTION CAMPAIGNS IN THE REPUBLIC OF KAZAKHSTAN AND FORMATION AND DEVELOPMENT OF TECHNOLOGIES (The Conference Hub, 2025)
In this article, the electoral system of the Republic of Kazakhstan, the laws adopted on elections are expressed in their content essence, the implementation of electoral processes of local self-government bodies.